IMPLEMENTASI SISTEM PENJAMINAN MUTU INTERNAL DALAM MENINGKATKAN MUTU LAYANAN PENDIDIKAN: Penelitian di Sekolah Model SPMI SD Darul Hikam 2 Kabupaten Bandung dan SDN 200 Leuwipanjang Kota Bandung - Tien Sulastri (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2020)
This research is motivated by the low quality of education in various education, so that the Quality of Internal Quality Assurance System of Education Services needs to be improved. The purpose of this study is to find out the standards, quality mapping, planning, implementation, evaluation, inhibiting strategy and supporting quality assurance in Darul Hikam 2 Elementary School and 200 Lew SDN in the city of Bandung. This study uses a qualitative approach with descriptive methods. as well as in-depth interviews and documentation. Data were analyzed through data reduction, data presentation, drawing conclusions, and testing the validity of the data by triangulation. The findings of this study that these two schools as a whole have implemented an internal quality assurance system in improving the quality of education services in their respective schools with good results because the lowest is in the range of 5.06 and that means including the category towards SNP 3 with 3 star acquisition .